Effect of dietary cholesterol on plasma cholesterol concentration in subjects following reduced fat, high fibre diet. Issue 6568 (7th February 1987) - Edington, J; Geekie, M; Carter, R; Benfield, L; Fisher, K; Ball, M; Mann, J
Abstract : One hundred and sixty eight subjects participated in a randomised crossover study to determine whether halving or doubling the present dietary cholesterol intake from eggs had any influence on blood cholesterol concentration in people following current dietary recommendations. During the first eight weeks all participants were advised to follow a reduced fat diet (26% total energy for hyperlipidaemic patients, 35% total energy for normolipidaemic volunteers) with an increased ratio of polyunsaturated to saturated fatty acids. This background diet was continued throughout the 16 week experimental period, during which participants ate either two or seven eggs a week. A small but significant increase in total cholesterol was seen after four weeks in the group eating seven eggs a week compared with that in the group eating two eggs a week, but this was no longer apparent after eight weeks. Previous studies suggesting that dietary cholesterol has a greater effect on the serum cholesterol concentration either have been carried out against a background of a higher fat intake or have contrasted extreme cholesterol intakes. A further reduction in dietary cholesterol seems to be unnecessary in those people who have already reduced their intake of saturated fat and increased the ratio of polyunsaturated to saturated fatty acids and fibre rich carbohydrate.